Towards a flexible Decision Support Tool for MSY-based Marine Protected Area design for skates and rays. (26th August 2016) - Dedman, Simon; Officer, Rick; Brophy, Deirdre; Clarke, Maurice; Reid, David G.
Abstract : It is recommended that demersal elasmobranchs be managed using spatial proxies for Maximum Sustainable Yield. Here we combine escapement biomass —the percentage of the stock which must be retained each year to conserve it—with maps of predicted Catch Per Unit Effort (CPUE) of four ray species [cuckoo ( Leucoraja naevus ), thornback ( Raja clavata ), blonde ( Raja brachyura ), and spotted ( Raja montagui )], created using Boosted Regression Tree modelling. We then use a Decision Support Tool to generate location and size options for Marine Protected Areas to protect these stocks, based on the priorities of the various stakeholders, notably the minimisation of fishing effort displacement. Variations of conservation/fishing priorities are simulated, as well as differential priorities for individual species, with a focus on protecting nursery grounds and spawning areas. Prioritizing high CPUE cells results in a smaller closed area that displaces the most fishing effort, whereas prioritizing low fishing effort results in a larger closed area that displaces the least fishing effort. The final result is a complete software package that produces maps of predicted species CPUE from limited survey data, and allows disparate stakeholders and policymakers to discuss management options within a mapping interface.